Case report: Prenatal diagnosis of rare chromosome mosaicism: discordant results between chorionic villi and amniotic fluid samples - Li, Lingping; Liu, Xijing; Li, Qinqin; Zhang, Lili; Xiong, Yueyue; Liu, Shanling; Wang, He; Zhu, Hongmei; Zhang, Xuemei (Frontiers in Genetics, 2023)
Objective: We described a unique case of near-negative chromosome mosaicism in chorionic villi but complete monosomy X in amniotic fluid. Methods: Chorionic villus sampling and amniocentesis were performed separately in the first and second trimesters. Chromosomal microarray (CMA) and rapid aneuploidy detection (QF-PCR and FISH) were performed on placental villi and uncultured amniotic fluid. After pregnancy termination, the placenta, umbilical cord, and fetal muscle tissues were sampled for FISH detection. Results: The CMA revealed a lower signal from chromosome X in chorionic villi, with a copy number of 1.85, implying the presence of mosaic monosomy X. However, the QF-PCR and FISH results were nearly normal. In uncultured amniotic fluid, CMA and rapid aneuploidy detection indicated complete monosomy X. Across different sampling points on the aborted fetus, the FISH results varied from normal, to mosaic, and then complete monosomy X. Conclusion: This case presents a rare and complex situation where sampling from uncultured chorionic villi indicated low-level chromosome mosaicism, while sampling from amniotic fluid revealed complete monosomy X. Although some of these discordant outcomes may be due to methodological limitations, we conclude that prenatal consultation should be combined with fetal ultrasound phenotype and genetic testing for a comprehensive evaluation of fetal genetic abnormalities.